Responses to Heat Stress Within an Unplanned Settlement in Dar Es Salaam, Tanzania - Adegun, Olumuyiwa Bayode; Mbuya, Elinorata Celestine; Njavike, Emmanuel (Frontiers in Built Environment, 2022)
Addressing the fallouts of a +1.5°C world is one of the key challenges for urban management in African cities. This article reports a work dealing with climate adaptation in informal urban settlements, with focus on responses to heat stress among the urban poor. The study involved a survey of 405 residents in Keko Machungwa —an unplanned neighborhood in Dar es Salaam, Tanzania. We found that the most popular behavioral responses are taking a shower, wearing light clothing,. drinking cold drinks, and opening doors and windows. The rarest forms of responses are swimming and contributing to savings group. Heat-related health problems experienced by the residents were also identified. Enhancing human responses to heat stress will involve improvement in basic services and infrastructure, awareness, and education among the residents.